Healthy choice label does not substantially improve consumers' ability to select healthier cereals: results of an online experiment. Issue 11 (22nd April 2019) - Siegrist, Michael; Hartmann, Christina; Lazzarini, Gianna A.
Abstract: The results of numerous studies suggest that front-of-package (FOP) labels enhance consumers' ability to assess the healthiness of food products. However, most of the studies lack ecological validity. We selected fourteen breakfast cereals stocked by a major Swiss retailer. The participants from an Internet panel ( n 780), with a somewhat higher educational level than that of the Swiss population, were randomly assigned to one of four conditions: control (picture of the FOP presented), table (plus the nutrition table with information on the energy and the main nutrients per 100 g), label (plus the healthy choice label for the healthier product) and combined (plus both the nutrition table and the healthy choice label). The participants were asked to select the healthier cereals from all possible ninety-one pair comparisons. The nutrient profile score was used as a 'gold standard'. For the thirty-three cereal pairs, one of the cereals had a label and the other had none, the median accuracy was only marginally lower in the control condition (91 %) compared with the table (94 %), the label (94 %) and the combined conditions (97 %). Similar results were observed when the incorrect decisions were weighted by the difference in the nutrient profile scores of the two cereals (for all ninety-one product pairs). These findings suggest that a healthy choice label has a limited effect on helping consumers select healthier cereals. In the control condition, the median of the correct choices was about 78 %. Consumers' perception of the healthiness of foods could be improved.